Mixing studies in unbaffled stirred tank reactor using electrical resistance tomography - Sardeshpande, Madhavi V.; Kumar, Gaurav; Aditya, T.; Ranade, Vivek V. (Flow Measurement and Instrumentation, 2016)
Unbaffled stirred tanks are extensively used in chemical process industries for variety of applications including semi-batch reactions. In un-baffled stirred tanks, impeller rotation generates a vortex and reactants are added into this vortex. There is a growing interest towards understanding the mixing performance of such unbaffled stirred vessels. The present work is aimed at providing experimental results on mixing time and solid particle distribution inside an unbaffled vessel using electrical resistance tomography (ERT). A methodology for using ERT for characterizing vortex and mixing in unbaffled stirred vessel was established. The ERT was used to measure the mixing time with and without solid particles (glass beads, 250 mu m) in a stirred reactor. In this study, ERT technique was effectively applied for imaging solid-liquid flow and developed suitable data processing methodologies. It observed that estimated liquid phase mixing time for Un-baffled vessel was more as compared to baffled vessel. Radial solid concentration profiles showed Gaussian distribution inside the vessel. The presented methodology of using ERT and experimental results will be useful for designing and estimating mixing and solid distribution in unbaffled stirred tanks. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: ERT; Mixing time; Radial solid concentration; Unbaffled stirred tank

Dual-catalyst engineered porous organic framework for visible-light triggered, metal-free and aerobic sp(3) C-H activation in highly synergistic and recyclable fashion - Kumar, Gaurav; Dash, Soumya Ranjan; Neogi, Subhadip (Journal of Catalysis, 2021)
Photoredox and organo-catalysis denote powerful construction tools for new classes of carbon-carbon bonds, where incisive amalgamation of both the approaches over a single, recyclable platform can bring about synergic and eco-friendly reactions under mild conditions. Aiming at enamine-based photoredox catalysis for atom-economic and metal-free sp(3 )C-H activation, an amide-based two-dimensional (2D) porous organic framework (POF) is devised. The pendent -NH2 groups are judiciously anchored with two catalytic stations viz. Rose Bengal and L-proline, through stepwise variation of solid phase peptide synthesis. The dual-catalyst engineered POF represents a fully organic material that synergistically performs visible-light triggered oxidative Mannich reaction to produce biorelevant heterocycle beta-amino ketone in excellent yield at room temperature, using oxygen as clean and selective oxidant. Importantly, activity of this bi-functionalized catalyst compares favorably well to individual homogeneous counterparts. The covalently modified framework demonstrates economic viability via gram-scale synthesis besides admirable reusability, and proves to be effective for nineteen varieties of substrates. The photocatalytic path is detailed from efficient energy transfer from host polymer to substrate in light of experimental and theoretical studies, which provides proof-of-concept to the photo-organo combined mechanism. The material benefits heterogenising two homogeneous catalysts, besides excluding additional steps of conventional Mannich reactions, and offers a step-forward to smart and green cross-dehydrogenative coupling reactions. (C) 2020 Elsevier Inc. All rights reserved.
Keywords: Atom-economy; C-H activation; Dual-catalyst engineering; Metal-free reaction; Photo-organo catalysis; Porous organic framework